2011
DOI: 10.3945/jn.110.135517
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus johnsonii N6.2 Stimulates the Innate Immune Response through Toll-Like Receptor 9 in Caco-2 Cells and Increases Intestinal Crypt Paneth Cell Number in BioBreeding Diabetes-Prone Rats

Abstract: Lactobacillus johnsonii (Ljo) N6.2 has been shown to mitigate the development of type 1 diabetes when administered to diabetes-prone rats. The specific mechanisms underlying this observed response remain under investigation. The objective of this study was to assess the effect of Ljo N6.2 on mucosal inflammatory response using differentiated Caco-2 monolayers. The mRNA expression levels of CCL20, CXCL8, and CXCL10 chemokines were determined by qRT-PCR. Ljo at 10(11) CFU/L induced a strong response in all chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 36 publications
4
63
0
Order By: Relevance
“…Diabetes prevention, in association with the upregulation of IL-17 immunity, could be explained by the ability of IL-17 to activate the anti-microbial response in combination with mucosal repair mechanisms [15]. It is also possible that other mechanisms are involved because Lactobacillus johnsonii affects epithelial integrity directly [16]. However, in NOD-mice, increased expression of colonic IL-17 was associated with the development of diabetes, and dietary prevention of diabetes was associated with down-regulation of colonic IL-17 [17].…”
Section: Abbreviationsmentioning
confidence: 99%
“…Diabetes prevention, in association with the upregulation of IL-17 immunity, could be explained by the ability of IL-17 to activate the anti-microbial response in combination with mucosal repair mechanisms [15]. It is also possible that other mechanisms are involved because Lactobacillus johnsonii affects epithelial integrity directly [16]. However, in NOD-mice, increased expression of colonic IL-17 was associated with the development of diabetes, and dietary prevention of diabetes was associated with down-regulation of colonic IL-17 [17].…”
Section: Abbreviationsmentioning
confidence: 99%
“…TLR9 signaling is associated with gut homeostasis, where loss of TLR9 signaling results in increased susceptibility to colonic inflammation (17). Further, TLR9 has been shown to be involved in the antiinflammatory effects of probiotics (13,20), demonstrating a role for probiotic bacteria DNA as an active factor that imparts a beneficial effect. More recently, Hall et al (8) have shown a role for TLR9 signaling and gut flora DNA in modulating the levels of T-regulatory and T-effector cells in the gut.…”
mentioning
confidence: 99%
“…Most effects have been attributed to an increase in the innate immune response and to others an increase in the acquired immune response. The innate immune system initiates a response to microorganisms or their components via pattern recognition receptors such as Toll-like receptors (TLR) or nucleotide-binding oligomerization domain-like receptors (Kingma et al, 2011) and previous studies have reported TLRs expression in blood Worku & Morris 2009). In our study, probiotics had an effect in the expression of TLR3 and TLR8 in goats, and increase in expression of TLR4, TLR6, TLR7 and TLR9.…”
Section: Discussionmentioning
confidence: 99%